2019
DOI: 10.1126/science.aav9011
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the heteromeric GluA1/2 AMPA receptor in complex with the auxiliary subunit TARP γ8

Abstract: AMPA-type glutamate receptors (AMPARs) mediate excitatory neurotransmission, and are central regulators of synaptic plasticity, a molecular mechanism underlying learning and memory. Although AMPARs act predominantly as heteromers, structural studies have focused on homomeric assemblies. Here we present a cryo-EM structure of the heteromeric GluA1/2 receptor associated with two TARP γ8 auxiliary subunits, the principal AMPAR complex at hippocampal synapses. Within the receptor, the core subunits arrange to give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(136 citation statements)
references
References 86 publications
7
128
1
Order By: Relevance
“…We have identified that the PPT1 depalmitoylation site for the GluA1 AMPA receptor subunit (GRIA1) is also on the extracellular domain. This extracellular site has not been previously identified, though other palmitoylation sites have been previously identified (Herguedas et al, 2019). The site we identified, (C323) typically forms a disulfide bond (to C75).…”
Section: Search For Structural Motifsmentioning
confidence: 61%
“…We have identified that the PPT1 depalmitoylation site for the GluA1 AMPA receptor subunit (GRIA1) is also on the extracellular domain. This extracellular site has not been previously identified, though other palmitoylation sites have been previously identified (Herguedas et al, 2019). The site we identified, (C323) typically forms a disulfide bond (to C75).…”
Section: Search For Structural Motifsmentioning
confidence: 61%
“…While the recent wealth of structural information on TARP/TARP-like complexes (Twomey et al, 2016, 2017a,b, 2018; Zhao et al, 2016, 2019; Chen et al, 2017; Herguedas et al, 2019) and claudins (Suzuki et al, 2014; Saitoh et al, 2015; Nakamura et al, 2019) has provided new insights into potential modulatory interfaces, the exact interactions are in fact ambiguous. The loops are often only visible at low thresholds in cryo-EM density maps, indicating that the loops are conformationally heterogeneous in the states that have been captured in structural studies and are not tightly bound.…”
Section: Discussionmentioning
confidence: 99%
“…Recent proteomics studies have identified >30 AMPAR regulatory proteins, which are structurally and functionally diverse (Schwenk et al, 2012; Shanks et al, 2012). In this review, we focus on the structure and function of claudin-fold auxiliary subunits, including TARPs, and advances in understanding their modulation of AMPAR function associated with recent developments in cryo-EM (Twomey et al, 2016, 2017a,b, 2018; Zhao et al, 2016, 2019; Chen et al, 2017; Herguedas et al, 2019). TARPs assemble around AMPARs at variable stoichiometry (Shi et al, 2009; Kim et al, 2010; Hastie et al, 2013; Twomey et al, 2016) but appear to share conserved assembly interfaces along the AMPAR TMD.…”
Section: Architecture Of Ampars and Ampar–tarp Complexesmentioning
confidence: 99%
“…These auxiliary proteins determine many biophysical and pharmacological properties of AMPARs and influence their desensitization 23,24 . The prototypical TARP -2 markedly slows the rate of AMPAR desensitization and accelerates recovery from desensitization 25,26 , while TARP -8 and GSG1L slow both the entry into and the recovery from desensitization 21,22,27 . The structures of desensitized complexes, composed of homomeric GluA2 AMPARs with either -2 or GSG1L, have recently been determined at~8 Å resolution by cryo-electron microscopy (cryo-EM) 16,19 .…”
Section: Introductionmentioning
confidence: 99%